Comparison of therapeutic outcomes of sorafenib and lenvatinib as primary treatments for hepatocellular carcinoma with a focus on molecular‐targeted agent sequential therapy: A propensity score‐matched analysis. Issue 4 (1st March 2021) - Tomonari, Tetsu; Sato, Yasushi; Tani, Joji; Hirose, Akira; Ogawa, Chikara; Morishita, Akihiro; Tanaka, Hironori; Tanaka, Takahiro; Taniguchi, Tatsuya; Okamoto, Koichi; Sogabe, Masahiro; Miyamoto, Hiroshi; et al.
Abstract: Aim: The optimal choice between sorafenib (SOR) or lenvatinib (LEN) as the first‐line treatment for unresectable hepatocellular carcinoma (u‐HCC) remains debatable. Using propensity score matching, this study compares the outcomes of SOR and LEN in the molecular‐targeted agent (MTA) sequential treatment of u‐HCC patients. Methods: This retrospective, multicenter, observational study recruited 137 u‐HCC patients who underwent primary treatment with LEN ( n  = 52) or SOR ( n  = 85) between June 2017 and June 2020 after regorafenib was approved as the secondary treatment for u‐HCC. Propensity score matching was used to reduce confounding, resulting in the selection of 104 patients ( n  = 52 for the SOR and LEN cohorts). Results: The median overall survival was 21.8 months for LEN and 20.4 months for SOR. LEN exhibited significantly greater therapeutic efficacy as compared to SOR (objective response rate: 3.8% [SOR] vs. 42.3% [LEN], p  < 0.01; progression‐free survival: 10 months [LEN] vs. 5.1 months [SOR], p  < 0.01). No significant intergroup differences were noted in the rate of transition to secondary MTA treatments (SOR: 58.7%; LEN: 48.4%), adverse events (SOR: 86%; LEN: 95%), and maintenance of the Child–Pugh (CP) score during treatment. Compared to non‐MTA treatments, secondary MTA treatment achieved a greater improvement in survival (4.3  vs. 2.8 months, p  = 0.0047). Multivariate analysis demonstrated that the CP score ( p  < 0.01) and alpha‐fetoprotein level ( p  < 0.01) were independent prognostic factors. Conclusions: Both SOR and LEN treatments showed a clinically comparable therapeutic efficacy as the first‐line treatments for u‐HCC patients in an MTA sequential therapy.